Tembang in Dolalak Performance Art: Structure, Meaning, and Deconstruction - Santosa, Djarot Heru (Universitas Negeri Makassar, 2017)
Dolalak is a type of folk performance art popular in the Purworejo Regency, Central Java Province. Its existence is often associated with another folk performance art called Angguk. Both forms of performance arts influence each other. Based on a study on a book written in 1938 by Th. Pigeaud with title on Javaanse Volksvertoningen (Javanese Folk Performance Arts), the name Angguk had been recorded at that time while Dolalak had not. Purworejo’s Dolalak was initially popularized by three santris (religious students) named Rejotaruno, Duliyat, and Ronodimejo. One of the popular elements of Dolalak performance is tembang. These tembangs are a form of sung folk poetry. It takes form in the oral language, using the Javanese language and containing elements. Up to 2010, found 210 Dolalak successful song lyric documented in writing. Besides poetry, the other elements of the song is a song. Dolalak song has a number of variations of the songs are quite unique and interesting when sang his poems. Discussion of the above problems, used an umbrella approach to Performance Studies (Art Studies appearance), was the study of the use of the song in the show Dolalak used models of Jacques Derrida's theory of deconstruction. Special analysis of linguistic elements used Dolalak song lyric theory proposed formula Albert B. Lord. Analysis begins with the deconstruction reveal pre-existing construction, namely the assertion that Dolalak the nuances of Islamic arts, especially seen from the use tembangnya. Starting from the existing construction, it found kontrakdisi of actual reality. Such contradictions give rise to ideas or a new offer in the way of understanding of Dolalak seen from the song and use. This research has resulted in findings that means a new understanding of Dolalak as folk performances seen from the use of poetry tembangnya, namely that Dolalak an art form that is simple, straightforward, uncomplicated, irregular, choose words that are popular, easily understood, and choose the theme of daily life. Song lyrics Dolalak more concerned with sound rather than sense or meaning. This condition reflects populist Dolalak as performance art.